A CLINICAL STUDY OF AGGRESSION AND GENERAL MENTAL AWARENESS OF VOLLEYBALL PLAYERS REPRESENTED AT THE INTER-UNIVERSITY LEVEL - Khandekar, Amitkumar Prabhakar; Raju Mahadev Raut (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Volleyball is a high-intensity, fast-paced sport that requires players to make quick decisions, perform technical skills accurately, and work efficiently with teammates. This puts players under a great deal of physical and mental stress while playing. This stress negatively impacts their performance. Mental stress affects their confidence and coordination of physical movements. Their decision-making ability is impaired due to increased aggression and anxiety while making important decisions during the competition. To perform successfully, volleyball players need to consistently deliver accurate serves, fast defensive play, and timely decision-making in a fast-paced and high-pressure competitive environment.